2020
DOI: 10.3389/fpsyg.2020.00812
|View full text |Cite
|
Sign up to set email alerts
|

On the Value of Considering Specific Facets of Interactional Justice Perceptions

Abstract: This research seeks to verify the value of considering specific perceptions of informational and interpersonal justice over and above employees' global perceptions of interactional justice. In Study 1 (Sample 1: n = 592; Sample 2: n = 384), we examined the underlying structure of workers' perceptions of interactional justice by contrasting first-order and bifactor representations of their ratings. To investigate the true added value of specific informational and interpersonal justice perceptions once global in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
2
5
0
Order By: Relevance
“…In particular, the identification of such a large (58.17% in the sample of mixed employees and 62.63% in the sample of nurses) Normative profile suggests that global levels of burnout remain minimal and aligned across dimensions for more than half of the participants. This finding is aligned with results from past studies of work engagement (Gillet et al, 2019a(Gillet et al, , 2020c, well-being and psychological health (Morin et al, , 2017, interactional justice (Fouquereau et al, 2020), emotional labor (Fouquereau et al, 2019) or need satisfaction (Gillet et al, 2019b), in which a similarly normative profile was also found to characterize a large proportion of employees.…”
Section: Employees' Burnout Profilessupporting
confidence: 89%
“…In particular, the identification of such a large (58.17% in the sample of mixed employees and 62.63% in the sample of nurses) Normative profile suggests that global levels of burnout remain minimal and aligned across dimensions for more than half of the participants. This finding is aligned with results from past studies of work engagement (Gillet et al, 2019a(Gillet et al, , 2020c, well-being and psychological health (Morin et al, , 2017, interactional justice (Fouquereau et al, 2020), emotional labor (Fouquereau et al, 2019) or need satisfaction (Gillet et al, 2019b), in which a similarly normative profile was also found to characterize a large proportion of employees.…”
Section: Employees' Burnout Profilessupporting
confidence: 89%
“…In particular, the identification of this profile suggests that global levels of workaholism remain minimal and aligned across dimensions for nearly a third of the sample in Studies 2 and 3. This finding is aligned with results from past studies of work engagement (Gillet, Caesens, et al, 2019;Gillet, Morin, Jeoffrion, et al, 2020), well-being and psychological health (Morin, Boudrias, et al, 2016;Morin et al, 2017), interactional justice (Fouquereau et al, 2020), emotional labour (Fouquereau et al, 2019) or need satisfaction , in which a similarly average profile was also found to characterise a significant proportion of employees.…”
Section: Workaholism Profilessupporting
confidence: 89%
“…This result is interesting given that prior variable-centered research has consistently positioned fairness as a positive driver of psychological health in a "the more, the better" perspective (e.g. Fouquereau et al, 2020;Greenberg & Cropanzano, 2001). Nevertheless, recent findings rather suggest a "too much of a good thing" interpretation according to which high levels of fairness perceptions might be detrimental in some situations (Brockner et al, 2009;Rodwell & Fernando, 2015;Tremblay et al, 2018).…”
Section: Job Demands and Resources As Predictors Of Profile Membershipmentioning
confidence: 76%